2022
DOI: 10.1038/s41598-022-20668-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of brain networks with three monochromatic wavelengths: a pilot study using resting-state functional magnetic resonance imaging

Abstract: Exposure to certain monochromatic wavelengths can affect non-visual brain regions. Growing research indicates that exposure to light can have a positive impact on health-related problems such as spring asthenia, circadian rhythm disruption, and even bipolar disorders and Alzheimer’s. However, the extent and location of changes in brain areas caused by exposure to monochromatic light remain largely unknown. This pilot study (N = 7) using resting-state functional magnetic resonance shows light-dependent function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…As represented by facts, in these four participants, violet-blue-green filters acted like inhibitors, causing depression of neuronal networks [33]. A global decrease in functional connectivity in most networks was found after a minute of green and blue light exposure through a fMRI study [28], which leads us to the same conclusion, namely, that these ranges of wavelengths can modify brain networks which are arranged to perform better on tasks associated with specific cognitive demands. An increment on the LAT DIFF LT-RT was observed in 58.3% of the cases, against 37.5% that presented a decrease in its value.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As represented by facts, in these four participants, violet-blue-green filters acted like inhibitors, causing depression of neuronal networks [33]. A global decrease in functional connectivity in most networks was found after a minute of green and blue light exposure through a fMRI study [28], which leads us to the same conclusion, namely, that these ranges of wavelengths can modify brain networks which are arranged to perform better on tasks associated with specific cognitive demands. An increment on the LAT DIFF LT-RT was observed in 58.3% of the cases, against 37.5% that presented a decrease in its value.…”
Section: Discussionsupporting
confidence: 58%
“…However, what we know from quantitative electroencephalography studies, is that light stimulation and phototherapy which employs a combination of two or more of these wavelengths (mu-alpha, omega-neurasthenic, alphaomega etc), can modulate the alpha-wave, interhemispheric connections, anteroposterior gradient, and brain coherence [26,27]. Likewise, a pilot study on healthy participants showed that functional connectivity patterns on brain networks measured with fMRI, are light-dependent [28]. Therefore, we expect to see the effect of these monochromatic filters on the visual pathway, which connects the eyes to the cortex and modulates neural activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the functional significance of EEG microstates ( Britz et al, 2010 ; Milz et al, 2016 ; Seitzman et al, 2017 ) have suggested that microstate A is associated with the auditory network, while microstate D is related to the dorsal attention network (DAN). A recent study using resting-state fMRI ( Argilés et al, 2022 ) also reported an alteration in the functional connectivity of the DAN after red light exposure. Moreover, several papers have reported significant enhancement of attention and memory induced by tPBM ( Barrett and Gonzalez-Lima, 2013 ; Hwang et al, 2016 ; Vargas et al, 2017 ; Jahan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, other studies such as Ibrahimi et al 1 have currently reported that the use of this light therapy may produce changes in the metrics of cortical activity in patients with strabismus and amblyopia. Argilés et al 24 have also reported that the use of Syntonic therapy can modify the functional connectivity of a broad range of visual and non-visual brain regions. Accordingly, even though some clinicians use phototherapy as a visual therapy for several visual conditions, there seems to be a lack of evidence about the efficacy of this technique.…”
Section: Introductionmentioning
confidence: 99%